TINGKAT KOMPETENSI PROFESIONAL PENYULUH PERTANIAN DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Rahmad Fauzan; Rosnita '; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
A competence of agricultural extension agents is the quality of each individual agents. The responsibility of each agricultural extension agents in Gunung Toar Subdistrict more than one vilage cause the load of tasks to complete will be heavier, this situation will affect quality and performance of the extension agent. The objectives of this research were: 1) find out  the implementation of extension, 2) analyze the competence level of extension agents and 3) to know the problems in improving the competence of extension agent. The research was conducted in Gunung Toar Subdistrict, Kuantan Singingi Regency. The respondents were the agricultural extension agents in UPTD Plantation Gunung Toar Subdistrict, they were selected by sensus and the amount of them are 5. Colection of the data was done by quisioner list and then analyzed using Likert's Summated Rating (LSR). The results showed that the level of competence of agricultural extension agent from UPTD Plantation Gunung Toar Subdistrict are classified as Competent that can be seen from the sub-variable administrative ability, program planning, program implementation, teaching ability, communication skills, understanding human behavior, the ability to maintain professionalism and evaluation. There are some problem in extension activity in order to improve the competence of agents, The problem are: formal education of agents  is still low, education and training received is still limited, working period of agent is still low, lack of media utilization as the tool of learning, the major lack of extension workforce, where ideally one village is suppose to have one agent. Keywords: Professional competence, Extension, Extension problems